2012
DOI: 10.1021/ie202478c
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Butadiene Adsorption over Transition Metal Polycation Exchanged Faujasites

Abstract: New adsorbents for butadiene removal from liquid and gas streams, which are transition metal (Cu, Zn, Mn) polycation exchanged zeolites, were prepared on the basis of low-silica and dealuminated faujasites by ion exchange with the corresponding salt solutions at the conditions of their partial hydrolysis. Obtained samples were characterized by XANES, ESR, and DRIFT spectroscopy along with equilibrium and dynamic adsorption studies. It is shown that transition metal polycation containing faujasites significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…. As the TrM polycation‐exchanged zeolite along with the polycations contain significant amounts of monocations, a relatively low change of the average Cu−O distance in the (Cu) p CaLSF sample versus the monocation Cu‐exchanged zeolites may give evidence of an essential increase of the reactivity of the Cu polycations.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…. As the TrM polycation‐exchanged zeolite along with the polycations contain significant amounts of monocations, a relatively low change of the average Cu−O distance in the (Cu) p CaLSF sample versus the monocation Cu‐exchanged zeolites may give evidence of an essential increase of the reactivity of the Cu polycations.…”
Section: Resultsmentioning
confidence: 85%
“…[11,19,20] Thea uthors also found that the reactive adsorption of 1,3-butadiene with the dimerization of the substrate over some Tr Mp olycation-exchanged low-silica faujasites (LSF) is responsible for the enhanced adsorption capacity of the applied adsorbent-catalysts. [21] Accordingly, it is reasonable to assume that the unusually high adsorption values for sulfur compounds displayed by Cu, Zn, and Mn polycation-exchanged zeolites [22,23] may result from as imilar catalytic-adsorption action. Thep resented inveistedi sd evoted to the study of the mechanism of the reactive adsorption of sulfur compounds by Tr Mp olycationexchanged zeolites and the clarification of the characteristic oxidizing role of the adsorbent-catalystsi nd esulfurization of gas and liquid hydrocarbonstreams.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations